Optimization and Validation of a Method to Determine Enolones and Vanillin Derivatives in Wines: Occurrence in Spanish Red Wines and Mistelles (2023)
Understanding the chemical nature of wine aroma demands accurate quantitative determinations of different odor-active compounds. Quantitative determinations of enolones (maltol, furaneol, homofuraneol, and sotolon) and vanillin derivatives (vanillin, methyl vanillate, ethyl vanillate, and acetovanillone) at low concentrations are complicated due to their high polarity. For this reason, this paper presents an improved and automated version for the accurate measure of these common trace wine polar compounds (enolones and vanillin derivatives). As a result, a faster and more user-friendly method with a reduction of organic solvents and resins was developed and validated. The optimization of some stages of the solid phase extraction (SPE) process, such as washing with an aqueous solution containing 1% NaHCO3 at pH 8, led to cleaner extracts and solved interference problems. Due to the polarity of these type of compounds, an optimization of the large volume injection was also carried out. Finally, a programmable temperature vaporization (PTV) quartz glass inlet liner without wool was used. The injector temperature was raised to 300 ◦C in addition to applying a pressure pulse of 180 kPa for 4 min. Matrix effects were solved by the use of adequate internal standards, such as ethyl maltol and 30 ,40 -(methylenedioxy)acetophenone. Method figures of merit were highly satisfactory: good linearity (r2 > 0.98), precision (relative standard deviation, RSD < 10%), high recovery (RSD > 89%), and low detection limits ( 1) while homofuraneol and sotolon could also produce changes in their aroma perceptions (0.1 < OAV < 1).